Digital Teaching Materials for Historical Narrative Texts Oriented to Character Education for SD/MI Students - Arji, Muhammad Romi; Kusmana, Suherli; Wilsa, Jaja (PT Inovasi Pratama Internasional, 2024)
This research aims to develop digital teaching materials for historical narrative texts oriented towards character education for SD/MI students. Background to the problem of this research 1) What is the need for digital teaching materials for historical narrative texts oriented towards character education for SD/MI? 2) How are digital teaching materials for historical narrative texts oriented towards character education for SD/MI? 3) What is the feasibility of digital teaching materials for historical narrative texts oriented towards character education for SD/MI? This research uses research and development methods with the ADDIE (Analysis Design Development Implementation Evaluate) model. The steps in this research consist of needs analysis, designing digital teaching materials, developing digital teaching materials, implementing digital teaching material products, and product evaluation (digital teaching materials). Data collection in this research was by collecting data from the results of expert validation questionnaires and student assessment questionnaires. The data obtained was analyzed descriptively using a Likert scale. The results of the validation test by material experts obtained a value of 2.93, the validation test by media experts obtained a value of 3.00. The validation test by the Indonesian language teacher received a value of 3.03. The results of implementing e-module teaching materials in schools received a positive response from students with a score of 3.2. The conclusion of this research is that digital historical narrative text teaching materials oriented towards character education for SD/MI students meet the appropriate criteria for use as teaching materials by students or teachers in Indonesian language subjects. Narrative text materials for fifth grade SD/MI students.